Deep Learning for Diagnostic Binary Classification of Multiple-Lesion Skin Diseases - Thomsen, Kenneth; Christensen, Anja Liljedahl; Iversen, Lars; Lomholt, Hans Bredsted; Winther, Ole (Frontiers in Medicine, 2020)
Background: Diagnosis of skin diseases is often challenging and computer-aided diagnostic tools are urgently needed to underpin decision making. Objective: To develop a convolutional neural network model to classify clinically relevant selected multiple-lesion skin diseases, this in accordance to the STARD guidelines. Methods: This was an image-based retrospective study using multi-task learning for binary classification. A VGG-16 model was trained on 16,543 non-standardized images. Image data was distributed in training set (80%), validation set (10%) and test set (10%). All images were collected from a clinical database of a Danish population attending one dermatological department. Included was patients categorized with ICD-10 codes related to acne, rosacea, psoriasis, eczema and cutaneous t-cell lymphoma. Results: Acne was distinguished from rosacea with a sensitivity of 85.42% CI 72.24%-93.93% and a specificity of 89.53% CI 83.97%-93.68%, cutaneous t-cell lymphoma was distinguished from eczema with a sensitivity of 74.29% CI 67.82%-80.05% and a specificity of 84.09% CI 80.83%-86.99%, and psoriasis from eczema with a sensitivity of 81.79% CI 78.51%-84.76% and a specificity of 73.57% CI 69.76%-77.13%. All results were based on the test set. Conclusion: The performance rates reported were equal or superior to those reported for general practitioners with dermatological training, indicating that computer-aided diagnostic models based on convolutional neural network may potentially be employed for diagnosing multiple-lesion skin diseases.